Biomechanical analysis of gait with double backpack - Santos, Jorge (2022)
When observing the gait associated with the transportation of backpacks by children and adults, there were differences in posture and gait when compared to gait without back overload. Using a backpack type double backpack, studies suggest its performance is better than traditional transport. It is expected to confirm the advantages of using double backpack by the civilian population for the transport of high loads minimizing possible future injuries.